Comparison of the Czech Republic’s Financial Soundness Against the Visegrad Group (V4) Between 2005–2022 - Srivastava, Anirudh; Bednář, Milan, 1991-; Pekárek, Štěpán; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2024)
Financial stability is an important topic not just to ensure the soundness of the banking sector but to also prevent any spillover effects on the economy as a whole that may have resulted due to inadequate planning, risk-seeking behavior, or simply lack of macroprudential policies. In the case of the Czech Republic, it is not a lesser-known fact that the country has maintained a high level of financial stability thus promoting financial soundness. The thesis aims to utilize the financial soundness indicators to find out the CAMEL (Capital Adequacy, Asset quality, earning ability Management Quality, and Liquidity) ratings for the Visegrad group (V4) members. The focus of the thesis is to compare this level of financial soundness against other V4 members between 2005 – 2022. The comparison can be important while formulating monetary or macroprudential policies within a country. A less financially stable member country has the probability to cause stress on a common system among the group and also other trading member states. The theoretical part highlights the development of financial stability, responsible institutions for supervision, and the macroprudential vision for the V4 members. Notably, the core importance of financial stability was only realized post-economic crises despite the presence of signals in the economy. The empirical part shall focus on the adherence of the V4 member countries to the Basel standards and the International Monetary Fund (IMF). Financial Soundness Indicators (FSIs), it can be seen that the Czech Republic maintains a sound level of financial stability. However, the country has its pitfalls in the areas of liquidity, capital markets, and a considerable foreign ownership share of the banking sector. The country performs well against the Western European banking sector but has areas of improvement when comparing the capital markets and the ROE.
It can be noted that the V4 members overall have a sound level of financial stability but certain countries experiencing volatility can cause stress on the overall system due to the inefficiencies observed in some areas of the banking sector in these countries. The thesis also uses an OLS regression model to find the effect of certain macroeconomic variables on the FSIs of the Czech banking sector, the results show us that the depreciation of the exchange rate can increase the NPL ratios of the country and decrease the ROE. Overall, the macroeconomic variables show an effect on the Czech banking sector’s FSIs but do not shift them by a large degree.
Vedoucí práce: Milan Bednář
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: economics and public policy [obor dipl. práce]; diplomové práce; master's theses